Construction and evaluation of validity and reliability of self-management questionnaire based on NAMAD design in adolescent girls of secondary school in Tehran - Khadijeh Abolmaali Alhosseini; Mina Atashsokhan (پژوهش در نظام‌های آموزشی, 2022)
The purpose of this research was to the development of self-management questionnaire based on the Social Care System of Students, and consider the validity and reliability of this questionnaire. The research method was descriptive of the survey type. The population consisted of high school girl students in non-Governmental schools in Tehran in the academic year of 2017-2-18. 300 students were selected by cluster random sampling and completed the researcher-made questionnaire. Confirmatory factor analysis was used to analyze the data. The fitting indices in the first step were not desirable. After items parceling using exploratory factor analysis, another confirmatory factor analysis was used, and the fitting indices indicated the suitability of the model with the data collected. Based on this, goal management skills, time management skills, change management skills, emotional management skills, communication management skills, self-control skills, self-regulation skills, and self-motivational management skills were confirmed. To verify the internal consistency of the self-management questionnaire and its components, Cronbach's alpha coefficient was used. The internal consistency of the entire questionnaire is equal to 9.23, and the internal consistency of the above-mentioned components were 0.78, 0.78, 0.68, 0.91, 0.86, 0.78, 0.71, 0, 0.75, respectively. The correlation coefficients between the components of the self-management questionnaire were positive and significant. The convergent validity and composite reliability of the questionnaire components were relatively acceptable. In attention to, the desirable psychometric properties of this questionnaire, it is recommended to school counselors and psychologists to use this questionnaire for measuring of self- management in female students.